Księgozbiory kościelne na terenie lwowskiej archidiecezji obrządku łacińskiego na przełomie XVIII/XIX w - Krętosz, Józef (Śląskie Studia Historyczno-Teologiczne, 2007)
The following article is an attempt to reconstruct the history of church collections of books, especially those belonging to the Polish monastries and parishes which were within the Austrian partition on the turn of the 19th century. The most drastic annihilation of the church libraries in Galitia and Lodomeria was done by the Josephian politic. In these times some orders and other “non-priestly” benefices were annulated. Those church institutions and their collections of books were sentenced for annihilation. The research aim of the article is to follow the history of church libraries belonging to the annulated monasteries. The problem will be illustrated by the history of the church libraries in the years 1780–1815 on the area of Lwów Archdiocese in Latin order.